The Implementation of Drill Method to Improve Student Skills on Wudu and Salat - Julhadi Julhadi; Sobhan Sobhan (AL-ISHLAH: Jurnal Pendidikan, 2023)
Fiqh learning with various materials contained in it is faced with a real problem; namely, students find it challenging to have the ability to apply the subject matter they get. They understand cognitively but are not able to affectively and psychomotor. Therefore, teachers must make a breakthrough by trying new things in the learning process. This study aims to describe the use of the drill method in improving the ability of students in the field of fiqh, especially wudu and salat materials. Research is carried out in the form of Classroom Action Research, which is research based on real conditions in the classroom. Data is collected through observations and documentation studies. This research was conducted in the form of Classroom Action Research based on real conditions in the classroom. Based on the results, in the first cycle, 10 students were unable properly perform Wudu and salat. Based on these conditions, the researcher re-planned using the drill method in teaching Wudu and salat. Observations in cycle II showed that it is necessary to continue in cycle III because, in cycle II, 4 students were not yet skilled in wudu and salat. After cycle III, 17 IV-graders have skills in carrying out practical worship. The results showed that the drill method effectively improved skills in carrying out practical worship.